Sedimentology and depositional environment of Awi formation Calabar flank, southeastern Nigeria (1999)
"A sequence of conglomerates, sandstones, siltstones, claystones carbonaceous shales and mudstones which rims the Oban Massif in the Calabar Flank, constitutes the Early Cretaceous (probably Aptian) Awi Formation In the southeastern Nigeria. Field studies and laboratory analyses were conducted on these sediments to determine their provenance and depositlonal environment. Field observations show that the sediments are grently dipping (.< 16°) in a southwesterly direction. They vary in thickness from thin to very thick beds and are laterally, discontinuous. The pattern of sedimentation is cyclic with fining upward sequences. The sediments are textually immature with angular to subangular grains dominating, thus indicating short distance transportation. The sandstones are medium to coarse-grained, poorly sorted, mostly leptokurtic, fine skewed and unimodal in distribution. They are subarkoslc with more than 70% quartz which are of Igneous and metamorphic origin while the associated claystones contain kaolinite. Heavy mineral assemblages show the presence of predominantly zircon, tourmaline, rutile, garnet and staurolite with a range of 66.7 to 96%. This indicates mature to superrnature sandstones and can be attributed to wet climatic conditions. The carbonaceous shales which grade into mudstone In some cases are non-fossillferous, poorly laminated, pyritized and rich in lignitised wood. All these indicate that sediments of Awi Formation were derived from the Oban Massif and deposited in environments ranging from channel lag and point bar to flood plain. "